Neuroticism and Somatic Complaints: Concomitant Effects of Rumination and Worry. Issue 4 (7th November 2018) - Denovan, Andrew; Dagnall, Neil; Lofthouse, George
Abstract : Background: Neuroticism is associated with inflated somatic symptom reporting. Worry and rumination are a cognitive concomitant of neuroticism and potentially mediate the neuroticism–somatic complaint relationship. Aims: The present study examined the degree to which worry and rumination mediated the relationship between neuroticism and somatic complaints. Method: A sample of 170 volunteers, recruited via convenience sampling, took part. Participants completed a series of self-report measures: the Eysenck Personality Questionnaire Revised-Short Form, Penn State Worry Questionnaire, the Ruminative Response Scale and the Somatic Symptom Scale-8. Results: Analysis revealed significant positive correlations between neuroticism, rumination and worry. Neuroticism, rumination and worry also correlated positively with somatic complaints. Using structural equation modelling, a mediational model indicated that rumination fully mediated the relationship between neuroticism and somatic complaints. Conclusions: Findings are consistent with the symptom perception hypothesis and have implications for healthcare in terms of managing individuals who present with multiple somatic complaints. Future research would benefit from adopting a longitudinal approach to test how rumination interacts with neuroticism and somatic complaints over time.